2021
DOI: 10.3389/fped.2021.682327
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Experience in Patients With JIA-Associated Uveitis in a Large Referral Center

Abstract: Objectives: To describe demographic, clinical and therapeutic findings of a large cohort of patients with JIA-associated uveitis in a nationwide referral pediatric rheumatology and uveitis center in Northern Italy.Methods: Retrospective study of 125 patients with JIA-associated uveitis followed from 2009 to 2019. Demographic and rheumatologic features including JIA ILAR classification, age at onset, and laboratory data were recorded. Ocular findings collected were: anatomic location of uveitis, laterality, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(77 citation statements)
references
References 27 publications
1
76
0
Order By: Relevance
“…Our findings showed that iridocyclitis is indeed an independent risk factor of band keratopathy development (adjusted OR, 9.509; 95% CI, 7.183–12.589; P < 0.001, Table 2 ). This finding is consistent with that in previous reports, which showed that band keratopathy was a common ocular complication (19.2%–38%) in patients with Juvenile idiopathic arthritis-associated uveitis ( 4 , 35 , 36 ). The exact pathophysiology of band keratopathy is unknown, but it may be associated with phosphate breakdown due to pH changes on the ocular surface.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings showed that iridocyclitis is indeed an independent risk factor of band keratopathy development (adjusted OR, 9.509; 95% CI, 7.183–12.589; P < 0.001, Table 2 ). This finding is consistent with that in previous reports, which showed that band keratopathy was a common ocular complication (19.2%–38%) in patients with Juvenile idiopathic arthritis-associated uveitis ( 4 , 35 , 36 ). The exact pathophysiology of band keratopathy is unknown, but it may be associated with phosphate breakdown due to pH changes on the ocular surface.…”
Section: Discussionsupporting
confidence: 93%
“…Histological analysis of affected corneas shows a fine granular calcification in the superficial cornea including the Bowman’s membrane and deep-situated calcium plaques involving the anterior stroma ( 1 , 3 ). A variety of factors are associated with band keratopathy, including chronic ocular conditions such as uveitis ( 4 , 5 ), silicon oil retention ( 6 , 7 ) and phthisis bulbi; and systemic condition such as diabetes mellitus (DM), chronic kidney disease (CKD) ( 8 ), elevated serum phosphate levels and increased serum calcium levels that are possibly related to secondary hyperparathyroidism ( 9 – 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uveitis and arthritis might have similar pathogenesis related to immune cell activation and TNF-a hyperproduction ( 18 , 19 ). Both arthritis and uveitis respond well to methotrexate and TNF-a inhibitors (adalimumab and infliximab) ( 20 ). Earlier prescription of methotrexate and biologics may decrease the incidence of uveitis ( 21 – 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As modern medicine advances by leaps and bounds, the prognosis of JIA has improved dramatically. However, certain children are afflicted with severe complications such as loss of joint function, lifelong eye damage owing to uveitis, and macrophage activation syndrome (MAS), which may be fatal ( 5 , 6 ). Therefore, effective early diagnostic biomarkers or models of JIA are highly sought after.…”
Section: Introductionmentioning
confidence: 99%
“…The role of N 6 -methyladenosine modification in immunity is increasingly being appreciated. However, the landscape of m 6 A regulators in juvenile idiopathic arthritis (JIA) is poorly understood.…”
mentioning
confidence: 99%